Brand Perception Towards PERODUA Car : Myvi / Salinah Morni - Morni, Salinah (2005)
The Perusahaan Otomobil Nasional Bhd (PROTON) is closely linked to the history of the auto industry in Malaysia according to Dilip Singh Mutum in his article on an Overview of the Malaysian Auto Industry. Incorporated on May 7, 1983 to manufacture, assemble and sell motor vehicles and related products, including accessories, spare parts and-other components. Obstacles to production efficiency in local motor vehicle assembly operations and also in the marketing of automobiles in Malaysia was pointed out by researchers Sim, Keat and Li (DiIip,2005) . This includes diseconomy of scale associated with production oriented to a domestic market oflimited size and lack of Customer focus. According to him the Malaysian Government later with the direct support of Tun Dr Mahathir Mohamad, the former Prime Minister of Malaysia initiated the national car project. These helped to create employment and has helped establishment of supportive industries. It created a number of companies solely dedicated to making specialized accessories such as sports rims, tints, and scores of workshops. Now, Malaysia holds a dominant position in vehicle sales among ASEAN countries and has become one of the region's largest auto markets.